Prior to Peripheral Tolerance, Newly Generated CD4 T Cells Maintain Dangerous Autoimmune Potential: Fas- and Perforin-Independent Autoimmunity Controlled by Programmed Death-1 - Ellestad, Kristofor K.; Thangavelu, Govindarajan; Haile, Yohannes; Lin, Jiaxin; Boon, Louis; Anderson, Colin C. (Frontiers in Immunology, 2018)
Lymphopenia can result from various factors, including viral infections, clinical interventions, or as a normal property of the fetal/neonatal period. T cells in a lymphopenic environment undergo lymphopenia-induced proliferation (LIP) to fill the available “niche” as defined by peptide–MHC and homeostatic cytokine resources. We recently reported systemic autoimmunity following reconstitution of the lymphoid compartment of Rag1−/− mice with PD-1−/− hematopoietic stem cells or by transfer of thymocytes, but not splenocytes, suggesting that programmed death-1 (PD-1) plays a crucial role in controlling recent thymic emigrants (RTE) and preventing autoimmunity upon their LIP. However, it is unclear whether RTE residing within the periphery of a lymphoreplete host maintain enhanced autoimmune generating potential or if this property only manifests if RTE experience a lymphopenic periphery immediately after export from the thymus. Furthermore, it is unclear which of a variety of T cell effector mechanisms generate pathology when control of RTE by PD-1 is lacking. Herein, we determined that PD-1 is upregulated on CD4 T cells undergoing the natural LIP characteristic of the neonatal period. Newly generated T cells lacking PD-1 maintained an enhanced autoimmune potential even after residence in a lymphoreplete periphery, emphasizing the importance of PD-1 in the establishment of peripheral tolerance. Neither Fas nor perforin-dependent killing mechanisms were required for autoimmunity, while host MHC-II expression was critical, suggesting that LIP-driven autoimmunity in the absence of PD-1 may primarily result from a CD4 T cell-mediated systemic cytokinemia, a feature potentially shared by other autoimmune or inflammatory syndromes associated with immune reconstitution and LIP.